2023
DOI: 10.1093/rheumatology/kead348
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid treatment in SLE is associated with infections, comorbidities and mortality—a national cohort study

Abstract: Objectives Patients with SLE have an increased risk of comorbidities and impaired survival. We aimed to assess if various thresholds of oral corticosteroids (OCS) can predict development of infections, comorbidities, malignancies and survival in SLE using data from national health registries in Sweden. Methods All incident SLE cases, age >18 years, in Sweden (n = 5309) between 2005 and 2020 and matched population contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This is because even low doses of systemic glucocorticoid treatment are associated with an increased risk of infections, osteoporosis, and increased mortality. 25 In the current study, we observed a reduction in steroid use across patients, fulfilling one of the purposes of adding Anifrolumab to the standard of care in SLE treatment. Further, in 44% of cases, we could avoid reintroducing steroids during the patient's flare by adding Anifrolumab to standard of care.…”
Section: Baselinesupporting
confidence: 60%
“…This is because even low doses of systemic glucocorticoid treatment are associated with an increased risk of infections, osteoporosis, and increased mortality. 25 In the current study, we observed a reduction in steroid use across patients, fulfilling one of the purposes of adding Anifrolumab to the standard of care in SLE treatment. Further, in 44% of cases, we could avoid reintroducing steroids during the patient's flare by adding Anifrolumab to standard of care.…”
Section: Baselinesupporting
confidence: 60%
“…SLE patients, in fact, are a population at increased infection risk due to both the aberrant immune system and glucocorticoids and other immunosuppressants used to treat the disease. Although prognosis has considerably improved over the years, infections still remain a major cause of hospitalisation and mortality in patients with SLE, especially in the early phase of disease (56)(57)(58). Although controversial, the crucial interplay between SLE and infections must draw attention to the importance of preventive measures such as vaccination.…”
Section: Infectionsmentioning
confidence: 99%
“…Thus, SLE continues to represent a major challenge for both patients and physicians. Inappropriate or incomplete management of SLE disease activity and/or the side effects of administered therapies, particularly corticosteroids, may lead to comorbidities, irreversible organ damage, decreased health-related quality of life, and increased mortality [2][3][4].…”
Section: Introductionmentioning
confidence: 99%